Modifications of fungal membrane proteins profile under pathogenicity induction: A proteomic analysis of Botrytis cinerea membranome. Issue 17 (5th August 2016) - Liñeiro, Eva; Chiva, Cristina; Cantoral, Jesús M.; Sabidó, Eduard; Fernández‐Acero, Francisco Javier
Abstract : Botrytis cinerea is a model fungus for the study of phytopathogenicity that exhibits a wide arsenal of tools to infect plant tissues. Most of these factors are related to signal transduction cascades, in which membrane proteins play a key role as a bridge between environment and intracellular molecular processes. This work describes the first description of the membranome of Botrytis under different pathogenicity conditions induced by different plant‐based elicitors: glucose and tomato cell wall (TCW). A discovery proteomics analysis of membrane proteins was carried out by mass spectrometry. A total of 2794 proteins were successfully identified, 46% of them were classified as membrane proteins based on the presence of transmembrane regions and lipidation. Further analyses showed significant differences in the membranome composition depending on the available carbon source: 804 proteins were exclusively identified when the fungus was cultured with glucose as a sole carbon source, and 251 proteins were exclusively identified with TCW. Besides, among the 1737 common proteins, a subset of 898 proteins presented clear differences in their abundance. GO enrichment and clustering interaction analysis revealed changes in the composition of membranome with increase of signalling function in glucose conditions and carbohydrate degradation process in TCW conditions. All MS data have been deposited in the ProteomeXchange with identifier PXD003099 (http://proteomecentral.proteomexchange.org/dataset/PXD003099 ).